COVID-19 상황에서 초등 과학 전담 교사의 수업 운영 실태 및 인식 - 김성운; 양일호; 임성만; Kim, Seong-Un; Yang, Il-ho; Lim, Sung-man (대한지구과학교육학회지, 2020)
The purpose of this study is to investigate how elementary science specialized teachers operate and how they have a perception of the science class in the COVID-19 situation. The number of participants in the study is 21 who are dedicated to science subjects in 2020. 21 teachers were given an open survey of science classes and future directions in the COVID-19 situation, and 8 out of 21 teachers were interviewed in-depth on how and why they did so. As a result of the study, first, the science classes before and after COVID-19 of primary science teachers were different. Under the COVID-19 situation, teachers identified the characteristics of online and offline classes and operated them in a way that was specific to their characteristics. Second, there was a common perception of teachers' classes on the basis of this science class operation style, which is that science classes should be operated as activities, that I would like to have classes that suit my taste as long as the policy allows, and that online classes cause students to lose motivation and widen their educational gap. 본 연구의 목적은 COVID-19 상황에서 초등 과학 전담 교사들은 과학 수업을 어떻게 운영하고 있으며 수업에 대해 어떤 인식을 갖고 있는지 조사하는 것이다. 연구 참여자는 2020년 과학 교과 전담교사를 맡고 있는 21명이다. 21명 전체를 대상으로 COVID-19 상황에서의 과학 수업과 앞으로의 수업방향에 대한 개방형 설문을 실시하였고, 21명 중 8명을 대상으로 과학 수업을 어떻게 하고 왜 그렇게 했는지등에 대한 면담을 실시하였다. 연구 결과, 첫째, 초등 과학 교사들의 COVID-19 이전과 이후의 과학 수업은 달랐다. COVID-19 상황에서 교사들은 온라인 수업과 오프라인 수업의 특성을 파악하고 특성에 따른 방식으로 운영하였다. 둘째, 이러한 과학 수업 운영 방식의 바탕에는 교사의 수업에 대한 공통된 인식이 있었으며, 그 인식은 과학 수업은 탐구 활동으로 운영해야 한다는 것, 방침이 허락하는 한, 내 입맛에 맞는 수업을 하고 싶다는 것, 온라인 수업은 학생들의 동기 저하 및 학력 격차 확대를 야기하며 이를 극복해야 한다는 것이다.